Knowledge of Sexually Transmitted Diseases Among College Students in the USA - Zahra Amirkhanzadeh Barandouzi; Xiaomei Cong (Iran University of Medical Sciences, 2019)
Background: Sexually Transmitted Diseases (STDs) are among the most prevalent infectious diseases in young people. The present study assessed the knowledge of STDs among college students.  Methods: This cross-sectional descriptive study that was conducted on 345 undergraduate students at a large public university in the United States. The students were recruited by convenience sampling method. The Sexually Transmitted Disease Knowledge Questionnaire (STD-KQ) was applied in the survey. The study participants responded to the survey anonymously through the Qualtrics online portal. Descriptive statistical analyses were conducted to examine the knowledge levels of the STDs in young adults. Independent Samples t-test and Analysis of Variance (ANOVA) were used to determine the correlation between the knowledge level and demographic data of the subjects. Moreover, SPSS was used for data analysis. Results: In total, 345 undergraduate students aged 18-22 years participated in the present study. Among them, 196 (56.8%) were male. The samples' Mean±SD score of STD knowledge was 15.66±5.84 (out of 27 points in total). The study participants who previously received sexual education courses achieved higher knowledge scores, compared to the others. Conclusion: The study results revealed a lack of STD knowledge in young adults. There is a need for conducting educational programs among college students to improve their understanding of STDs etiology and prevention.